3466 Real-world diagnosis of chronic migraine in patients with cervical dystonia analyzed by botulinum neurotoxin treatment exposure: an epidemiologic perspective - Rodriguez, Ramon; Broner, Susan W; de, Grace; Rhyne, Christopher; Sadeghi Marjan; Xiaomeng Emma; Ukah Ahunna; Ifantides Kim Becker; Sarva Harini; Kidd, Juanita (BMJ neurology open, 2025)
BackgroundMigraine is a common comorbidity in patients with cervical dystonia (CD); however, the diagnosis of chronic migraine (CM) in patients with cervical dystonia (CD) is unknown.MethodsThis observational retrospective cohort study used longitudinal patient-level data from the Optum Market Clarity Database in the US. CD cohort includes patients ≥18y with ≥2CD diagnoses ≥30d apart during the study (January 2017 - September, 2021) and ≥180d of continuous health plan enrolment prior to cohort entry (first CD diagnosis coding). Cohort 1:CD+migraine/headache patients; cohort 2: CD+CM patients; cohorts 3 and 4: CD+CM BoNT treated and BoNT-untreated patients, respectively. Assessments include diagnosis, demographics and clinical characteristics of migraine/headache in the CD cohort.ResultsOf 81,884 CD patients, 36.1% had migraine/headache (cohort 1, n=29,533), 12.6% had concurrent CM (cohort 2, n=10,284). There were more CD+CM patients in cohort 4(BoNT-untreated) compared to cohort 3 (BoNT-treated) (57.4% vs 42.6%). Common comorbidities were comparable across cohorts 1–4 (neck pain, range: 63.6% - 78.8%; psychiatric conditions, range: 37.5% - 43.3%). The proportion of patients with psychiatric conditions in the CD+CM cohort was greater compared to the overall CD cohort (42.9% vs 28.1%). CD+CM patients treated with BoNT for both CD and CM diagnoses were higher (24.6%) than those treated for CD or CM individually (19.6% and 16.6%)ConclusionThis study provides evidence that CM is a common comorbidity in CD patients and therefore underscores the importance of diagnosis and selection of appropriate treatment options for managing these disease states.